DETERMINANT OF EMISSION CARBON DISCLOSURE WITH INDEPENDENT BOARD OF COMMISSIONERS AS MODERATION IN INDONESIAN MANUFACTURING COMPANIES - Munawar Muchlish; Dirvi Surya Abbas (Jurnal Bisnis dan Akuntansi, 2024)
Good disclosure of carbon emissions can be an indication that the company has carried out operational activities in accordance with community norms. Companies that gain legitimacy from the public can attract investors to invest their capital. Sales of a company's products can increase if it has gained the trust of the public. The purpose of this study was to determine the effect of environmental performance, growth earnings, audit committee, on emission carbon disclosure with board of independent commissioners as moderating. Researchers use quantitative research. The population in this study were all companies in the manufacturing sector listed on the Indonesia Stock Exchange totaling 201 companies which were always listed for 4 consecutive years. The sample was selected using purposive sampling and obtained 60 research objects. The results of the study environmental performance, and growth earnings have an effect on emission carbon disclosure, while the audit committee has no effect on emission carbon disclosure. Board of commissioners as moderating is able to strengthen the effect influence of the environmental performance, and growth earnings and audit committee on the emission carbon disclosure.